2006
DOI: 10.1590/s1415-43662006000400015
|View full text |Cite
|
Sign up to set email alerts
|

Contaminação de águas superficiais por agrotóxicos em função do uso do solo numa microbacia hidrográfica de Agudo, RS

Abstract: Realizou-se este trabalho com o intuito de quantificar a presença de moléculas de agrotóxicos em águas superficiais de três unidades paisagísticas (UP) com diferentes configurações de uso, numa microbacia hidrográfica de cabeceira em Agudo, RS. Dois coletores semi-automáticos de água foram instalados no córrego de cada UP, onde se coletaram amostras, por ocasião de chuvas, em três épocas da cultura do fumo: transplante, aterramento junto aos pés da cultura (planta com 6-10 folhas) e colheita. Os princípios ati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 7 publications
(8 reference statements)
2
28
0
14
Order By: Relevance
“…Santos et al (2008) in a study conducted in shallow waters around the rice-growing areas in Rio Grande do Sul showed that 90% of samples contained clomazone residues. Bortoluzzi et al (2006) found the presence of this product in surface water adjacent to tobacco crops. The presence of clomazone in water and soil samples have been reported in the literature not only in Brazil but also in other countries such as Spain (Nevado et al, 2007), Italy (Palmisano & Zambonin, 2000), China (Li et al, 2010), Uruguay (Carlomagno et al, 2010) and United States (Gunasekara et al, 2009).…”
Section: Herbicides -Properties Synthesis and Control Of Weeds 152mentioning
confidence: 95%
“…Santos et al (2008) in a study conducted in shallow waters around the rice-growing areas in Rio Grande do Sul showed that 90% of samples contained clomazone residues. Bortoluzzi et al (2006) found the presence of this product in surface water adjacent to tobacco crops. The presence of clomazone in water and soil samples have been reported in the literature not only in Brazil but also in other countries such as Spain (Nevado et al, 2007), Italy (Palmisano & Zambonin, 2000), China (Li et al, 2010), Uruguay (Carlomagno et al, 2010) and United States (Gunasekara et al, 2009).…”
Section: Herbicides -Properties Synthesis and Control Of Weeds 152mentioning
confidence: 95%
“…Apesar de poucos estudos de monitoramento, a ATZ vem sendo encontrada em alguns mananciais (BORTOLUZZI et al, 2006;LAABS et al, 2002 (PROSAB, 1999).…”
Section: Filtração Lenta Associada a Carvão Ativado Granularunclassified
“…Herbicides are chemicals and usually synthetic compounds used to control weeds and increase the productivity of agricultural systems. However, they may be harmful to human and animal life, and may be transported from the soil to waters by surface draining and percolation (Kaufmann et al, 2012).In the state of Rio Grande do Sul, surface water often contain herbicides used in rice paddies (Primel et al, 2005;Sarcinelli, 2005;Bortoluzzi et al, 2006;Fernandes Neto and Sarcinelli, 2009).…”
Section: Introductionmentioning
confidence: 99%